1999
DOI: 10.1038/sj.bjc.6690140
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine and vindesine in patients with previously untreated non-resectable non-small-cell lung cancer

Abstract: Summary Because both vindesine and gemcitabine are active drugs in advanced non-small-cell lung cancer (NSCLC), with different modes of action and only partly overlapping toxicity, a phase II study was performed. Gemcitabine 1000 mg m -2 was given on days 1, 8 and 15 every 4 weeks, while vindesine 3 mg m -2 was administered weekly for 7 weeks, then every 2 weeks. A total of 42 patients with nonresectable NSCLC were included. The median age of patients was 56 years; 57% were men, 52% had adenocarcinoma, 31% squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…Our results contrast with those reported by Sorensen et al [14], who tested GEM and VDS in previously untreated NSCLC patients and reported an overall response rate of 20% and a median survival of 31 weeks, with greater hematological and non-hematological toxicity, and a worse quality of life. However, their schedule consisted of GEM 1000 mg/m 2 on day 1,8 and 15, and VDS 3 mg/m 2 every week for the first 7 weeks and then every other week.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our results contrast with those reported by Sorensen et al [14], who tested GEM and VDS in previously untreated NSCLC patients and reported an overall response rate of 20% and a median survival of 31 weeks, with greater hematological and non-hematological toxicity, and a worse quality of life. However, their schedule consisted of GEM 1000 mg/m 2 on day 1,8 and 15, and VDS 3 mg/m 2 every week for the first 7 weeks and then every other week.…”
Section: Discussioncontrasting
confidence: 85%
“…This variation of the Sorensen regimen [14] was designed to reduce the risk of hematological (neutropenia and thrombocytopenia) and non-hematological toxicity (paresthesias).…”
Section: Treatmentmentioning
confidence: 99%